THE BIOMASS OF TROPICAL ANCHOVIES (Encrasicholina SPECIES) AT BACAN, EASTERN INDONESIA ESTIMATED BY THE DAILY EGG PRODUCTION METHOD - David A. Milton; Retno Andamari; Nicholas J.F. Rawlinson (Research Center for Fisheries, 1998)
Tropical anchovies (Encrasicholdno species) are the target of the large baitfishery for the pole-and-line skipjack tuna fleet in eastern Indonesia. Recent studies have shown that the tuna catches are constrained by a lack of bait.